BAG-1 stabilizes mutant F508del-CFTR in a Ubiquitin-Like-Domain-Dependent Manner - Mendes, Filipa (2013)
Cystic Fibrosis Transmembrane Conductance Regulator (CFTR), the dysfunctional Cl- channel in Cystic Fibrosis, undergoes complex biosynthesis at the endoplasmic reticulum involving several molecular chaperones including Hsp70 and many co-chaperones. Bcl-2-associated athanogenes (BAGs) constitute a protein family sharing an Hsc70-binding domain. BAG-1 possesses an ubiquitin-like domain (Ub-LD) responsible for proteasomal association and for promoting substrate release from Hsc70/Hsp70 in vitro by accelerating the chaperone ATP/ADP exchange rate. Methods: Herein, we studied the in vivo effect of BAG-1 on the turnover and processing of wild type (wt)- and F508del-CFTR, the most frequent mutation in CF patients. Results: Results show that BAG-1 associates with both wt- and F508del-CFTR (in higher yields with the latter) through its Ub-LD and independently of Hsc70. Moreover, the immature form of F508del-CFTR (but not of wt-CFTR) is stabilized by BAG-1 overexpression, albeit in a cell-type specific way, without detectable maturation. Data also show that BAG-1 and the proteasome inhibitor ALLN are not additive on stabilizing F508del-CFTR and this effect depends on BAG-1 Ub-LD. Moreover, under BAG-1 overexpression, a reduction in ubiquitinylated-CFTR occurs suggesting that BAG-1 competes with Ub. Conclusion: Overall, data are compatible with a mechanism in which BAG-1 stabilizes F508del-CFTR by direct binding, probably competing out ubiquitin to partially avoid its proteasomal degradation.